Processing and characterization of transparent ceramics - Goh, Nicholas Chung Min (2017)
Light scattering in ceramic materials has prevented the use of polycrystalline ceramics with anisotropic optical properties in applications such as special windows worked under extream conditions (very high/low temperature, high pressure). Further development in processing technology has allowed for very low porosity and fine grains, significantly improving transparency and is paving the way for polycrystalline ceramics to be used in demanding optical applications. We present a method for producing highly transparent MgO doped Al2O3 using Solid State Reaction with pressure-less sintering. In order to measure the light transmission properties, we use a Ultraviolet-Visible Spectroscopy while we test the mechanical properties by using Vickers Hardness Test. It was found that the addition of MgO could suppress the exaggerate grain growth of Al2O3 ceramics. Doping with MgO could help eliminating residual pores and obtaining fine-grained Al2O3 transparent ceramics. Hardness of the Al2O3 transparent ceramics was also improved thanks to the controlling of grain growth.